Identification of Vibrio cholera and Detection of ompW Gene in Isolates of Raw Vegetables from Kuching, Sarawak - Manin, Rantai (Universiti Malaysia Sarawak (UNIMAS), 2010)
Vibrio cholerae abundantly exist in aquatic sources. Ingestion of pathogenic V. cholerae O1 and O139 which generally found in raw and undercooked seafood can cause severe and sometimes lethal diarrheal disease called cholera. Therefore, an appropriate evaluation of existence of V. cholerae strain in selected V. cholerae isolates from raw vegetable samples in Kuching area is important. This study was attempted to detect ompW gene which is a virulence factors of V. cholerae. A total of 50 V. cholerae isolates were enriched in Luria Bertani (LB) broth and the isolation were performed via Thiosulfate Citrate Bile Sucrose (TCBS) agar. Then, forty presumptive V. cholerae isolates were subjected to morphological and biochemical tests. Furthermore, Polymerase Chain Reaction (PCR) amplification was performed specifically for ompW gene detection. Among 40 V. cholerae isolates, there was no presence of ompW gene. PCR results supported by biochemical test results indicate that all the isolates are not V. cholerae. This study suggests a low occurrence of V. cholerae in raw vegetables.